Design, simulation, fabrication and characterization of mass microsensors embeddable to an implantable microvalve for glaucoma treatment - Zalazar, Martín Ángel (2014)
Fil: Zalazar, Martín Ángel. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.